Innovation Snack Crackers Sorghum, Challenge and Characterization Product: A review - Evita Riviani Achmadi (Journal of Food and Agricultural Product, 2022)
Abstract Background : Snack crackers can be modified into healthy snacks with the concept of gluten-free crackers for coeliac sufferers. The best design innovation for producing gluten-free snack crackers is the use of sorghum flour as an alternative to wheat. Sorghum is recommended to be safe for coeliac sufferers because it is included in the Panicoidea sub family, which is the same family as corn and millet grains. The phenolic components contained in sorghum include 3-deoxyanthocyanins, proanthocyanidins, flavones and flavanones. These components are active components that act as antioxidants, anticarcinogens and prevent cardiovascular disease. Along with these functional components, the use of sorghum flour in crackers means they can be promoted as gluten-free snacks that provide health benefits.Scope and approach: This review explain about how to develop snack crackers that contain sorghum flour as the main ingredient and the challenging in terms of formulation and processing methods. Key to the success of cracker innovation with sorghum flour is establishing which cracker characteristics are accepted by consumers, critical points at the processing stage and characteristics of sorghum flour that support the desired end product.Key findings and conclusion: Development in formulations, ingredients and process conditions is a challenge for snack cracker innovation with sorghum flour as an alternative. Presence of some antinutritional factors in sorghum such as tannins, phytates, trypsin inhibitors, and protein crosslinker can be maintain by pretreatment sorghum before its prosessed as sorghum flour. The best treatment is fermentation followed by the combination of soaking, germination, and nixtamalization. Formulation and process condition can be adjust based on viscoelasticity and consistency of snack krekers dough. It is also important to consider incorporation sorghum flour and others gluten free flour to get optimum dough consistency and viscoelasticity. Increasing the viscoelasticity of the dough can be achieved by adding functional ingredients such as protein isolate, fibre, hydrocolloid and emulsifier to improve the baking quality of gluten-free snack crackers. The incorporation of optimization hydrocolloids and other functional ingredients requires further research focused on identifying the right functional ingredients to effectively replace the function of wheat gluten. Development of gluten-free crackers is expected to be able to overcome the limitations of technology, nutritional quality and sensory properties on an ongoing basis.